Interactive Multimedia "Melajah Cecimpedan Bali" for Elementary School Students Based on Android - Putra, Putu Satria Udyana; Murpratiwi, Santi Ika; Adnyana, I Nyoman Widhi; Meinarni, Ni Putu Suci; Sari, Ni Wayan Yunita (Jurnal Multidisiplin Sahombu, 2024)
Bali is famous for its strong and inherent culture in an area, one of which can be seen from the traditional arts that are still preserved by the community. Cultural heritage in the form of traditional arts in Bali still has a lot to be developed, preserved by the community and the younger generation. One of Bali's cultural heritage is Cecimpedan which is a Balinese puzzle. In an increasingly advanced era, traditional arts are beginning to be forgotten by the younger generation. One of the efforts that can be made so that culture in the form of traditional arts is preserved in the global flow that is advancing from year to year, through the use of interactive learning media in the learning process. The purpose of this research is to introduce cecimpedan to the younger generation, that learning traditional arts in the form of Balinese cecimpedan is no less fun than learning modern culture. The data obtained in this study from observation, questionnaires, and interviews. Based on the results of the questionnaire with a percentage of 97.2% or 72 respondents stated that the material presented in this interactive multimedia application is easy to understand.